Shallow Depth, Substantial Change: Fluid-Metasomatism Causes Major Compositional Modifications of Subducted Volcanics (Mariana Forearc) - Albers, Elmar; Shervais, John W.; Hansen, Christian T.; Ichiyama, Yuji; Fryer, Patricia (Frontiers in Earth Science, 2022)
Mass transfer at shallow subduction levels and its ramifications for deeper processes remain incompletely constrained. New insights are provided by ocean island basalt (OIB) clasts from the Mariana forearc that experienced subduction to up to ~25–30 km depth and up to blueschist-facies metamorphism; thereafter, the clasts were recycled to the forearc seafloor via serpentinite mud volcanism. We demonstrate that the rocks were, in addition, strongly metasomatized: they exhibit K2O contents (median = 4.6 wt.%) and loss on ignition (median = 5.3 wt%, as a proxy for H2O) much higher than OIB situated on the Pacific Plate, implying that these were added during subduction. This interpretation is consistent with abundant phengite in the samples. Mass balance calculations further reveal variable gains in SiO2 for all samples, and increased MgO and Na2O at one but losses of MgO and Fe2O3* at the other study site. Elevated Cs and Rb concentrations suggest an uptake whereas low Ba and Sr contents indicate the removal of trace elements throughout all clasts. The metasomatism was likely induced by the OIBs’ interaction with K-rich fluids in the subduction channel. Our thermodynamic models imply that such fluids are released from subducted sediments and altered igneous crust at 5 kbar and even below 200°C. Equilibrium assemblage diagrams show that the stability field of phengite significantly increases with the metasomatism and that, relative to not-metasomatized OIB, up to four times as much phengite may form in the metasomatized rocks. Phengite in turn is considered as an important carrier for K2O, H2O, and fluid-mobile elements to sub-arc depths. These findings demonstrate that mass transfer from subducting lithosphere starts at low P/T conditions. The liberation of solute-rich fluids can evoke far-reaching compositional and mineralogical changes in rocks that interact with these fluids. Processes at shallow depths (<30 km) thereby contribute to controlling which components as well as in which state (i.e., bound in which minerals) these components ultimately reach greater depths where they may or may not contribute to arc magmatism. For a holistic understanding of deep geochemical cycling, metasomatism and rock transformation need to be acknowledged from shallow depths on.